PENGEMBANGAN MASYARAKAT ISLAM: PROGRAM MAGRIB MENGAJI KECAMATAN KOTO TANGAH PADANG, SUMATERA BARAT - Fadjri Wahyu (Alfuad: Jurnal Sosial Keagamaan, 2018)
This study aims to describe the implementation of magical recitation at the Al-qur'an Rabbani foundation. Islamic society is a community that lives according to Islamic law. The Maghrib Mengaji Community Movement in Koto Tangah District in the last 3 years has not been effective. The availability of teaching staff and community participation in the Pengaji Maghrib Community Movement is one of the causes of the ineffectiveness of the implementation of the Maghrib Mengaji Community Movement. The purpose of the Maghrib Mengaji Community Movement activates Muslims to learn and read the Koran at sunset and make the religious community accustomed to reading the Qur'an and having a strong religious character in Koto Tangah District. From the results of the research analysis it can be concluded that the Maghrib Mengaji Community Movement is categorized as unsuccessful. This can be seen from the failure to achieve the desired goals and objectives, such as activating tahfiz houses and directing Muslims to study and read the Koran at maghrib and make religious and accustomed people to read Al-Quran and have strong religious character in Koto Tangah District. Factors that influence the success of the policy are found, namely: the availability of teaching staff and community participation.